Performance Measurement of Islamic Banking Based on Maqashid Shariah Using The Approaches of Islamic Social Reporting, Intellectual Capital, and Shariah Compliance: Pengukuran Kinerja Perbankan Syariah Berbasis Maqashid Syariah Dengan Pendekatan Islamic Social Reporting, Intellectual Capital, dan Shariah Compliance - Wahyudi, Muhamad; Rokhaniyah, Siti; Sasviranti, Aprilya Retno (Perisai : Islamic Banking and Finance Journal, 2025)
This study aims to analyse the performance of Islamic banks using a maqashid sharia-based approach that is audited with Islamic Social Reporting (ISR), Intellectual Capital, and Shariah Compliance to create a holistic performance measurement, in line with islamic values. This study uses the Systematic Literature Review (SLR) method to review various previous studies related to the implementation of Maqashid Sharia in Islamic Banking at the national and international levels. The results show that the use of maqashid sharia approach provides a more comprehensive evaluation than conventional methods such as CAMELS, which only focuses on financial indicators. Islamic Social Reporting plays an important role in reflecting the social responsibility of islamic banks, while effective Intellectual Capital management encourages innovation and increased competitiveness. Shariah Compliance is also a key pillar in ensuring all bank operations run in accordance with the principles of islamic law. However, several studies show that the implementation of these three elements has not been optimal in some institutions, which causes the impact on Maqashid Syariah performance to vary.